Mechanical vibrations of magnetically levitated viscoelastic droplets - Temperton, Robert H.; Hill, Richard J.A.; Sharp, James S. (Royal Society of Chemistry, 2014)
The mechanical vibrations of magnetically levitated droplets were investigated using a simple optical deflection technique. Droplets of water and a water-based solution of poly(acrylamide-co-acrylic acid) were levitated in the bore of a superconducting magnet and perturbed with a short puff of air. Centre of mass and surface vibrations were monitored using laser light refracted through the droplet, focussed on to the end of an optical fiber and detected using a photodiode. Time dependent variations in the voltage generated by the photodiode were Fourier transformed to obtain the frequency and spectral width of the drops' mechanical resonances. A simple theory of drop vibration was developed to extract the rheological properties of the droplets from these quantities. The resulting values of G' and G" that were extracted were found to be in good agreement with values obtained using conventional rheology techniques.